2022
DOI: 10.1155/2022/5479215
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Learners’ Adoption of an Educational Metaverse Platform: An Empirical Study Based on an Extended UTAUT Model

Abstract: This study examined the factors affecting learners’ adoption of an educational metaverse platform using an extended UTAUT (unified theory of acceptance and use of technology) model and incorporating perceived risk. Data were derived from a survey of 495 respondents from China and analyzed using structural equation modeling. The results revealed that (i) performance expectancy, effort expectancy, social influence, and facilitating conditions had significantly positive effects on learners’ satisfaction with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 103 publications
(150 reference statements)
0
25
0
Order By: Relevance
“…In other words, whether the concept of metaverse is understood correctly by educators is determined by descriptive studies such as metaphor analysis or evaluation of educational experiences in the metaverse (Lopez-Belmonte et. al, 2022;Teng et. al, 2022;Tutgun-Ünal, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, whether the concept of metaverse is understood correctly by educators is determined by descriptive studies such as metaphor analysis or evaluation of educational experiences in the metaverse (Lopez-Belmonte et. al, 2022;Teng et. al, 2022;Tutgun-Ünal, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the transition from the social media generation to the metaverse generation, it is important to consider the concept of metaverse and how the education system will be transformed in this process, in terms of creating an understandable road map. The transformation of the social media world into a new form integrating with metaverse will drag people into a digital game, and thus the education system will have to be redesigned and transformed in this gamified environment (Rospigliosi, 2022;Teng, 2022;Tarhan & Tutgun-Ünal, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They found that effort expectancy did not significantly influence behavioral intention. However, in a study conducted byTeng et al (2022), which examined the TA B L E 1 5 Path coefficients, total effects, and significance levels.…”
mentioning
confidence: 99%
“…havioral intention positively. Similarly,Chiao et al (2018) also found that social influence positively impacted behavioral intention.According toChiao et al (2018), using technology by peers will influence participants' behavioral intentions Teng et al (2022),. who examined educational metaverse environments for students, showed that social influence impacted usage intention Teng et al (2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation